Peran Dukungan Teman Sebaya dengan Motivasi Berhenti Merokok pada Remaja di MTs Al Hamidiyyah WringinJajar - Annisa Lutfiana; Iwan Ardian; Nutrisia Nu’im Haiya (Journal of Health, Medical, and Psychological Studies, 2025)
This study aimed to analyze the role of peer support in smoking cessation motivation among adolescents at MTs Al Hamidiyyah WringinJajar. A quantitative empirical study with a cross-sectional design was conducted in August 2025. The population consisted of all ninth-grade students who smoked, totaling 55 respondents, and total sampling was applied. Peer support was measured using a 20-item questionnaire, while motivation to quit smoking was assessed using the Richmond Test. Data were analyzed using univariate and bivariate analysis, with Somers’ d test applied at a significance level of α = 0.05. The findings showed that most respondents had moderate peer support and moderate motivation to quit smoking. Statistical analysis revealed a significant positive relationship between peer support and smoking cessation motivation, indicating that higher levels of peer support were associated with stronger motivation to quit smoking. These results highlight the importance of social influences in shaping adolescents’ health-related motivation. Strengthening positive peer support within the school environment may serve as an effective strategy to enhance smoking cessation motivation among adolescents and support healthier behavioral change.